INTERVENSI GIZI SPESIFIK PENCEGAHAN STUNTING PADA BALITA 24-59 BULAN DI PUSKESMAS SURADADI KABUPATEN TEGAL - Vilda Ana Veria; Venny Riska Utami (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Stunting is still a health problem that must be considered, one of which is in Indonesia. Suradadi Public Health Center is a health center located in the area of Tegal Regency. A total of 346 toddlers were stunted. One of the programs to deal with stunting is a specific intervention program. The purpose of this study was to evaluate a stunting-specific intervention program for infants aged 24 -59 months at the Suradadi Public Health Center.This study is a descriptive-analytic study with a cross-sectional approach on 96 toddlers from a population of 2,200 children aged 24-59 months in the Suradadi Health Center, Tegal Regency, from October 2020 to July 2021. The research variables studied were for specific interventions in prevention. Stunting includes vitamin A supplementation, zinc supplementation, integrated management of sick toddlers, immunization, and nutritional status based on the TB/U Z-score. Data collection with interview techniques and KIA book observation. Descriptive data analysis using SPSS software.The program's implementation that is explored is the practice carried out by both officers and mothers of children under five. The details of the programs that have been implemented include vitamin A supplementation (54%), zinc supplementation (82.3%), integrated management of sick toddlers (77.1%), and mandatory primary immunization (80.2%). Most of the toddlers were male (57.1%), aged 36-47 months (39.6%), Z-score TB/U was normal (90.6%), and all received exclusive breastfeeding as many as 96 toddlers ( 100%). The results of the specific intervention program at the Suradadi Health Center in vitamin A have reached the expected target. In providing zinc supplements, the coverage is still 60% due to the lack of availability of funds from the center. In the service of sick toddlers who use the IMCI guidelines, it still reaches 99% due to the pandemic, and in the provision of immunizations, it has reached the expected target.Based on the results of this study, it is recommended for the public health center to carry out routine monitoring in specific intervention programs for stunting prevention to achieve the targets that have been set. Specific intervention programs must also comply with the guidelines for implementing integrated stunting reduction interventions in districts or cities.